PEMANFAATAN E-COMMERCE TERHADAP MINAT BERWIRAUSAHA MAHASISWA AKADEMI KESEJAHTERAAN AKK YOGYAKARTA - Mrs Istiqomah (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2020)
ABSTRACT The E-commerce system that serves as a medium of purchase, sale, dissemination of information, marketing of goods and services. This reason arises as one of the obstacles of a person fostering entrepreneurial interest. The purpose of this research is to know the influence of E-Commerce Utilization on Entrepreneurial Interests. This type of research uses descriptive quantitative research This research was conducted in June 2020. The population in this study was 110 students of AKK Yogyakarta Welfare Academy. Samples in this study were taken with a random sampling system of 30 students who took entrepreneurial courses. Instruments use questionnaires in google form media. Data analysis techniques use simple linear regression analysis. The results showed that the significance level of 5% (0.000<0.005) so that it can be concluded that there is a positive and significant influence between the utilization of e-commerce on entrepreneurial interests and the increasing utilization of e-commerce will encourage greater entrepreneurial interest in AKS-AKK students